The Role Of Translation In The Dialogue Of Civilizations : West/islamic World - Mouna Mallem (The Journal of Studies in Language, Culture and Society, 2024)
Globalization created a state of cultural diversity, which became an essential condition of human society. This new reality increased the interrelatedness among all countries and cultures. Consequently, the inter-civilizational dialogue became necessary for global peace and common prosperity. The lack of communication can be considered as the major reason that leads to other phenomenon like racism, xenophobia, ethnocentrism, or even more serious issues like clash of civilizations. For that reason, the focus of dialogue of civilizations spread from security (like political and military fields), and social and economic fields into the area of culture which is more likely to promote exchange and mutual learning. This paper will discuss how translation, -which refers to the process of transferring written texts from one language to another-, as a means of interlingual communication works to exchange information between speakers of different languages which helps them know and understand each other. It will clarify its role in linking users of different languages to humanity and international society as it allows them to read both current publications and classics in their mother language. The paper will also investigate the role of translation in fighting stereotypes and prejudices about the cultural “Other” by providing unbiased texts through which the latter is presented. Knowing that the ultimate goal of the dialogue of civilizations is the realization that all civilizations are different but equal. Translation can help correct the illusion of Western dominance and its cultural supremacy by showing that no civilization is better but all civilizations experience periods of rise and fall .Translation helps people from different cultures see the consequences of the natural states of rise and fall through several disciplines like history ,science ,literature,...etc. The paper will provide examples of translated books that helped change the minds and broaden horizons. It will focus on the Western/Muslim dialogue.